F.P. Ramsey : critical reassessments - Frápolli, María José, 1960- (Continuum studies in British philosophy., 2005)
Frank Plumpton Ramsey (1903-1930), Cambridge mathematician and philosopher, was one of the most brilliant people of his generation. He lived in an extraordinarily stimulating milieu, surrounded by figures such as Russell, Whitehead, Keynes, Moore, and Wittgenstein. Ramsey's highly original papers on the foundations of mathematics, probability, economics, philosophy of science and the theory of knowledge were very influential in the 20th century and are still widely discussed in the 21st. Perhaps two of Ramsey's achievements outshine all the rest. One is his treatment of the theoretical terms of.